(untitled) (Western Pacific Surveillance and Response, 2021)
Problem: The novel coronavirus disease 2019 (COVID-19) pandemic adversely affected the preparation of Malaysia’s National Health and Morbidity Survey for 2020 because conducting it would expose data collectors and participants to an increased risk of infection. Context: The survey is nationally representative and community based and is conducted by the Institute for Public Health, part of the National Institutes of Health, to generate health-related evidence and to support the Malaysian Ministry of Health in policymaking. Its planned scope for 2020 was the seroprevalence of communicable diseases such as hepatitis B and C. Action: Additional components were added to the survey to increase its usefulness, including COVID-19 seroprevalence and facial anthropometric studies to ensure respirator fit. The survey’s scale was reduced, and data collection was changed from including only face-to-face interviews to mainly self-administered and telephone interviews. The transmission risk to participants was reduced by screening data collectors before the survey and fortnightly thereafter, using standard droplet and contact precautions, ensuring proper training and monitoring of data collectors, and implementing other administrative infection prevention measures. Outcome: Data were collected from 7 August to 11 October 2020, with 5957 participants recruited. Only 4 out of 12 components of the survey were conducted via face-to-face interview. No COVID-19 cases were reported among data collectors and participants. All participants were given their hepatitis and COVID-19 laboratory test results; 73 participants with hepatitis B and 14 with hepatitis C who had been previously undiagnosed were referred for further case management. Discussion: Preparing and conducting the National Health and Morbidity Survey during the COVID-19 pandemic required careful consideration of the risks and benefits, multiple infection prevention measures, strong leadership and strong stakeholder support to ensure there were no adverse events.